Amplified Local Cooling Potential of Forestation in Eastern Ethiopia’s Arid Lowlands under Climate Change: Insights from Dire Dawa, Shinile, and Somali Regions - Belay Sitotaw Goshu; Yonas Tadesse Alemu (Britain International for Academic Research (BIAR) Publisher, 2026)
This study investigates the biophysical cooling effects of forestation in eastern Ethiopia’s arid lowlands, Dire Dawa, Shinile, and Somali regions, amid climate warming, using satellite-derived data (MODIS, ERA5-Land) from 2003–2023 and CMIP6 projections to 2080 under SSP2-4.5 and SSP5-8.5 scenarios. Pairwise comparisons of land surface temperature (LST), evapotranspiration (ET), and albedo between forested and open lands (grassland, cropland, shrubland) revealed a mean cooling effect of 3.5–4.0 °C, driven primarily by enhanced ET (1,250–1,350 mm/year in dry seasons) offsetting albedo-induced warming (+18–24 W/m²). Seasonal dynamics showed amplification during dry periods (up to 4.5 °C), with Theil-Sen trends indicating a 0.14–0.18 °C/decade increase in cooling, linked to soil moisture declines (-0.004 m³/m³/decade). Structural equation modeling confirmed ET’s dominance (β=0.72 for ΔLST), though albedo’s role rises to 40% by 2080 under high emissions due to stomatal closure reducing ET by 15–20%. Projections forecast sustained amplification (4.2–4.7 °C) under moderate scenarios with 15% tree cover increase, but diminution (3.2–3.7 °C) under high emissions. Spatial analysis highlighted groundwater-dependent efficacy, strongest in Somali’s rangelands. Findings underscore forestation’s potential for heat mitigation, supporting initiatives like Ethiopia’s Green Legacy and Right Tree in the Right Place projects, while emphasizing adaptive strategies to balance water competition and albedo effects for climate-resilient land management.